Spilt Milk - Sara Matani MD; J. Rush Pierce MD, MPH (SAGE Publishing, 2015)
We report a case of bilateral chylothorax without evidence of chylous fistula in a 62-year-old man following total laryngectomy and bilateral selective neck dissection for laryngeal cancer. Chylous fistulae, a well-known complication of neck dissection, occurs following 1% to 2% of these surgeries. On rare occasions, the chyle leak may communicate with the pleural space, resulting in chylothorax. This is a rare but potentially life-threatening complication. Bilateral chylothorax following neck dissection is even rarer, with less than 25 cases reported in the literature. Early diagnosis is essential to prevent complications. Physicians should have a high index of suspicion, especially when the postoperative effusions do not respond to diuretics. Though no evidence-based treatment guidelines exist, expert opinion recommends conservative management as first-line therapy. Our patient was effectively treated by conservative management. We postulate a mechanism whereby bilateral chylothorax occurred in our patient without a chylous fistula.